(untitled) (Journal of the College of Basic Education, 2024)
The Iraqi Communist Party was considered one of the active Iraqi parties in the political history of Iraq, and it had an influential role in the Iraqi arena, especially since it carried the banner of defending the working class, or what it called in its literature the toiling people, or (the proletariat). Therefore, it is not surprising if they joined under its banner and leadership. At the beginning of its formation, it was formed by a number of members of the working class, but this does not mean that it is the only party that adopted the concerns of the Iraqi working class and defended it. Abdul Razzaq Al-Safi is considered the most prominent figure of the Iraqi Communist Party who fought to achieve the goals and principles in which he believes. He began his political activity early in his life when he was a student in the College of Law, and his political positions varied depending on the events that Iraq witnessed in the late royal era. . Opening words (Party - Iraq - Communist - Royalist)